2019
DOI: 10.1111/tpj.14319
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport pathways in isolated chromoplasts from Narcissus pseudonarcissus L.

Abstract: During daffodil flower development, chloroplasts differentiate into photosynthetically inactive chromoplasts having lost functional photosynthetic reaction centers. Chromoplasts exhibit a respiratory activity reducing oxygen to water and generating ATP. Immunoblots revealed the presence of the plastid terminal oxidase (PTOX), the NAD(P)H dehydrogenase (NDH) complex, the cytochrome b 6 f complex, ATP synthase and several isoforms of ferredoxin-NADP + oxidoreductase (FNR), and ferredoxin (Fd). Fluorescence spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…al. 25 using a step gradient in which chromoplasts accumulate at the 15 % / 30 % sucrose interphase 27 . The isolated chromoplasts were suspended in 100 mM Tris/HCl pH 7.4, 10 mM MgCl2, 1 mM 1,4-dithioerythritol.…”
Section: Methodsmentioning
confidence: 99%
“…al. 25 using a step gradient in which chromoplasts accumulate at the 15 % / 30 % sucrose interphase 27 . The isolated chromoplasts were suspended in 100 mM Tris/HCl pH 7.4, 10 mM MgCl2, 1 mM 1,4-dithioerythritol.…”
Section: Methodsmentioning
confidence: 99%
“…When plants are deficient in iron, the photosynthetic rate decreases, which leads to the disintegration of thylakoids, which inhibits photosynthesis. At the same time, the carotenoid and ferredoxin contents in the chloroplast pigment protein complex also decrease, which inhibits the synthesis of chloroplast precursors and reduces the chlorophyll content [ 44 ]. In this study, the active Fe and chlorophyll contents of camphor trees supplemented with deferoxamine increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In duckweed ( Lemna minor ), with increasing treatment concentrations, the color of duckweed leaves gradually turned yellow, and the content of chlorophyll and carotenoids decreased significantly (Sallah-Ud-Din et al, 2017 ). Studies on Arabidopsis thaliana showed that chloroplast ribosomal recycling factors played an important role in chloroplast biosynthesis, and changes in maize protein under chromium stress suggested that chloroplast ribosomal recycling factors may be involved in the structure of chloroplast under chromium stress through post-translational modifications (Wang et al, 2013 ; Grabsztunowicz et al, 2019 ). Most of the identified chromium stress proteins (72%, 42/58) were predicted to be localized in the chloroplast, and these chloroplast-localized chromium stress proteins were associated with chloroplast structure and function, including the participation in photosynthesis electron transport, chloroplast organization, chlorophyll biosynthesis, and chloroplast redox balance.…”
Section: Effects Of Chromium-induced Stress On Plant Growth and Devel...mentioning
confidence: 99%